Investigation of the enhanced oil recovery potential of sodium cocoyl alaninate: an eco-friendly surfactant - Tackie-Otoo, B.N. (Springer Science and Business Media Deutschland GmbH, 2022)
Amino acid-based surfactants (AASs) and other novel surfactants have recently gained attention to provide a favorable environmental image (âgreenâ) in surfactant application. Yet their potential in enhancing oil recovery is not well investigated. Only a few works have been reported on their potential enhanced oil recovery (EOR) application with less satisfactory results. Here in, sodium cocoyl alaninate (SCA), an acylated amino acid with excellent properties that facilitate its application in other fields, is investigated for its EOR potential. Its effectiveness in lowering the interfacial tension and the emulsifying crude oilâbrine mixture were studied. The ability to alter rock surface wettability and its adsorption behavior on the sand surface were studied as well. Then, its oil recovery potential was confirmed through a core displacement experiment. All studies were performed in comparison with conventionally deployed sodium dodecyl sulfate (SDS). The critical micelle concentrations for SCA (CMC = 0.23Â wt) and SDS (CMC = 0.21Â wt) were close, which serves as a good basis for comparing their EOR potential. SCA proved to be more effective in IFT reduction attaining a minimum IFT of 0.069Â mN/m (i.e., ~ 98.8 IFT reduction) compared to 0.222Â mN/m of SDS (i.e., ~ 96.2 IFT reduction) at the same concentration. Salinity showed a synergistic effect on the interfacial properties of both SCA and SDS but had a more significant impact on SDS interfacial properties than SCA due to low salt tolerance of SDS. The low IFT attained by SCA yielded enhanced emulsion formation and stable emulsion both at 25Â Â°C and 80Â Â°C for a period of one week. SCA also altered quartz surface wettability better via reduction of contact angle by 94.55 compared to SDS with contact angle reduction of 87.51. The adsorption data were analyzed with the aid of various adsorption isotherm models. The adsorption behavior of SCA and SDS could be best described by the Langmuir model. This means a monomolecular surfactant layer exists at the aqueousârock interface. SDS also exhibited more severe adsorption on the sand surface with the maximum adsorption density of 15.94Â mg/g compared to SCA with the maximum adsorption density of 13.64Â mg/g. The core flood data also confirmed that SCA has a better oil recovery potential than SDS with an additional oil recovery of 29.53 compared to 23.83 of SDS. This additional oil recovery was very satisfactory compared to the performance of other AAS that have been studied. This study therefore proves that SCA and other AAS could be outstanding alternatives to conventional EOR surfactants owing to their excellent EOR potential in addition to their environmental benign nature. Â© 2022, The Author(s).